Chemoselective and Direct Functionalization of Methyl Benzyl Ethers and Unsymmetrical Dibenzyl Ethers by Using Iron Trichloride. Issue 9 (23rd January 2014) - Sawama, Yoshinari; Goto, Ryota; Nagata, Saori; Shishido, Yuko; Monguchi, Yasunari; Sajiki, Hironao
Abstract Methyl and benzyl ethers are widely utilized as protected alcohols due to their chemical stability, such as the low reactivity of the methoxy and benzyloxy groups as leaving groups under nucleophilic conditions. We have established the direct azidation of chemically stable methyl and benzyl ethers derived from secondary and tertiary benzyl alcohols. The present azidation chemoselectively proceeds at the secondary or tertiary benzylic positions of methyl benzyl ethers or unsymmetrical dibenzyl ethers and is also applicable to direct allylation, alkynylation, and cyanation reactions, as well as the azidation. The present methodologies provide not only a novel chemoselectivity but also the advantage of shortened synthetic steps, due to the direct process without the deprotection of the methyl and benzyl ethers.